88.8k views
4 votes
For f(x)=3x and g(x)=x+1(f o g)(x) =?

User MasterFly
by
5.1k points

1 Answer

4 votes

Answer


(f\circ g)(x)=3x+3

Step-by-step explanation

The composite function can be rewritten as:


(f\circ g)(x)=f(g(x))

meaning that we have to replace all the x in f(x) with g(x).

In our case:

• f(x) = 3x

,

• g(x) = x+1

Then, we can write and simplify it as:


(f\circ g)(x)=3(x+1)
(f\circ g)(x)=3x+3

User Nican
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.